Serial five-membered lactone ring ions in the treatment of Alzheimer’s diseases-comprehensive profiling of arctigenin metabolites and network analysis - Li, Yanan; Lan, Xianming; Wang, Shaoping; Cui, Yifang; Song, Shuyi; Zhou, Hongyan; Li, Qiyan; Dai, Long; Zhang, Jiayu (Frontiers in Pharmacology, 2022)
Arctigenin is a phenylpropanoid dibenzylbutyro lactone lignan compound with multiple biological functions. Previous studies demonstrated that arctigenin exerted neuroprotective effects in vivo and in vitro in Alzheimer’s disease (AD) models; however, its metabolism in vivo was not studied. Traditional analytical methods only realise the partial characterisation of prototype drug metabolites, so there is a pressing need for a strategy to enable comprehensive drug metabolism depiction. In the present study, ions fishing with a serial five-membered lactone ring as a fishhook strategy based on ultrahigh-performance liquid chromatography-Q-Exactive Orbitrap mass spectrometry (UHPLC-Q-Exactive Orbitrap MS) was utilised to characterise the metabolism of arctigenin, which addressed the challenge of creating a thorough metabolic profile of neolignan. Firstly, data acquisition was performed in the full scan mode and depended on multiple mass defect filtering and dynamic background subtraction techniques to capture all the probable metabolites. Secondly, phase I and phase II metabolites were obtained using Compound Discoverer 3.1 software. Finally, five-membered lactone ring (m/z 83 [M-H]- / m/z 85 [M+H]+) or related fragment ions (m/z 57 [M-H]- / m/z 59 [M+H]+; m/z 101 [M-H]- / m/z 103 [M+H]+; m/z 55 [M-H]- / m/z 57 [M+H]+; m/z 67 [M-H]- / m/z 69 [M+H]+; m/z 39 [M-H]- / m/z 41 [M+H]+) were used as a hook to screen accurate metabolites. Based on the proposed strategy, a total of 105 metabolites were detected and characterised, among which 76 metabolites were found in rats, while 49 metabolites were characterised in liver microsomes. These metabolites were presumed to be generated through oxidation, reduction, hydrolysis, and composite reactions. As a result, arctigenin would undergo extensive phase I and phase II metabolism after entering the biological system. Subsequently, Network pharmacology was utilised to elucidate the mechanism of arctigenin and its main metabolites against Alzheimer’s disease, which involved 20 major signal pathways and 381 potential targets. The study on the comprehensive metabolism of arctigenin provides an overall metabolic profile, which will help to understand better the pharmacological mechanism of arctigenin in the treatment of Alzheimer’s disease (AD) and provide a basis for comprehension of the safety and toxicity of arctigenin.